Exiting foster care: a case study of former foster children enrolled in higher education in Kansas - Schwandt, Jamie R. (Kansas State University, 2013)
In the United States, foster care is provided to children to avert maltreatment and abuse of children in distressed families by providing a temporary home or a foster home. Courts with jurisdiction over families have been charged by Congress to find appropriate homes when necessary circumstances occur. In fiscal year 2009, there were 423,773 children in foster care (U.S. Department of Health and Human Services, 2010). When the term “foster child or foster care” is used, most individuals view the term as negative. Most statistical data reaffirms this belief and casts a negative light on the foster care system in the United States. Foster children exit the foster care system and face higher rates of substance abuse, unemployment, and incarceration, and lower educational attainment. Though foster children do suffer from uncertainty of shattered relationships, there are success stories that arise from foster care. This study examines the discovery of strengths and emerging possibilities in the State of Kansas foster care system and the conditions that make them possible. This study identifies and examines success stories of 15 former foster children in the State of Kansas and analyzes how to build on those success stories. This case study uses qualitative methods such as audio-taped interviews and an interview protocol with a pre-determined set of open-ended questions. This study identifies stories of effectiveness in the State of Kansas foster care system.
Keywords: Foster care; Emancipation; Higher education; Kansas; Educational attainment; Success; Educational leadership (0449); Education Policy (0458); Higher Education (0745)